The Influence of Risk Perception, Smoking Fatwa Knowledge, and Smoking Behavior on the Intention to Quit Smoking in Adolescents - Ayuning Tyas; Retnaningsih Retnaningsih (Journal of Consumer Sciences, 2025)
Background: The percentage of adolescent smokers is increasing; however, survey results indicate that many adolescent smokers express a desire to quit. Purpose: This study aims to analyze the effects of risk perception, smoking fatwa knowledge, and smoking behavior on the intention to quit smoking. Method: This cross-sectional study involved 100 Muslim adolescents aged 13-18 years who had actively smoked within the past three months. Risk perception was measured across five dimensions: functional, financial, physical, psychological, and social. Knowledge of the smoking fatwa refers to the fatwa issued by the Indonesian Ulema Council (MUI). Findings: The results showed that the highest perceived risk was functional risk, while the lowest was social risk. Only 32% of participants were aware of the fatwa issued by the MUI. On average, participants smoked 6.3 cigarettes per day, and 81% were classified as light daily smokers. Knowledge of the fatwa and the number of cigarettes smoked daily did not affect the intention to quit smoking. Perceived social risk had a positive effect on smoking cessation intention. Conclusions: Based on the results of the study, the factors influencing adolescents' intention to quit smoking include age, father's age, father's education, father's smoking status, social perceptions, and smoking-related expenditure. Research implications: The findings suggest the need for a holistic approach that targets adolescents at the individual, family, and community levels. Preventive, curative, repressive, and persuasive strategies are essential to promote smoking cessation intentions and reduce smoking behavior among adolescents.